Potensi Implementasi Education for Suistanable Development (ESD) Pada Konsep Dinamika Rotasi - Rohmawati, Qo'im; Roshayanti, Fenny (UPEJ Unnes Physics Education Journal, 2021)
This study aims to describe the potential results of the implementation of Education for Sustainable Development (ESD) on the concept of rotational dynamics. The research method uses a qualitative descriptive research type. The population in this study were 70 students of class XI MIPA at Madrasah Aliyah Negeri (MAN) Demak, Demak Regency. The research instrument was in the form of a check list of text/unit analysis questionnaires which were analyzed based on ESD indicators to obtain data and documentation techniques. The results of the study found that there is no curriculum in Indonesia that implements ESD in learning the material for the concept of Rotational Dynamics, this is indicated by the absence of the ESD perspective in learning tools. From the results of the analysis of the questionnaire given to respondents, the implementation of ESD on the concept of rotational dynamics has presented the ESD indicator with an average percentage of 33.12% in general, for socio-cultural aspects 35.81%, for environmental aspects 24.51% and 39.68% for the economic aspect. From the results of these studies, it is recommended to develop implementing ESD in learning with the concept of Rotational Dynamics.